Aflatoxin production on agricultural products - Kovács, Szilvia; Pusztahelyi, Tünde; Borbélyné Varga, Mária (Acta Agraria Debreceniensis, 2014)
Aflatoxins due to their toxicity pose significant economic and human health threat; therefore, it is important to avoid this type of contamination in agricultural products. Until now significant aflatoxin contamination occurred mainly in foods of tropical and subtropical origin because the optimal growth of the producer Aspergillus species is between 32–38 ºC. Nowadays the aflatoxin contamination is becoming higher threat in Hungary, due to the imported products, the rising average temperature and the climatic changes. There is a significant knowledge on the genetic and environmental effectors of the aflatoxin production; however, it is remained a great problem to control mold contamination and toxin production in farming and stock-raising. Here we attempted to summarize the knowledge on aflatoxin production and attempts of the elimination.